Evaluation of Endophytic Fungi from Medicinal Plants: Fusarium sp., Stagonosporopsis sp., and Penicillium as Potential Antagonists of Pathogenic Bacteria - Salma Jadallah; Abdlmanam Fakron; Hamad Hassn; Najat Salem (AlQalam Journal of Medical and Applied Sciences, 2025)
Antibiotic resistance (AMR) is one of the most serious global health challenges of the 21st century, calling for the search for natural alternatives to combat resistant bacteria. This study aimed to evaluate the antibacterial activity of some endophytic fungi isolated from the Cyrene region of Libya, including the species Stagonosporopsis sp. (PQ182696), Fusarium sp. (PQ178952), and Penicillium chrysogenum (PQ178955). Secondary extracts were obtained using ethyl acetate and tested against clinical isolates of Enterococcus spp. (PV606376) and Klebsiella pneumoniae (PV606419) using the disc diffusion method and minimum inhibitory concentration (MIC) test. The results showed that Fusarium sp. and Stagonosporopsis sp. extracts exhibited significant inhibitory activity, especially against Enterococcus spp. (with an inhibition zone of 2.89 ± 1.67 mm at 50% concentration), while the effect of Penicillium chrysogenum was weak and inconsistent. MIC values ranged between 125–150 µg/mL for Enterococcus spp. and 160–175 µg/mL for K. pneumoniae, indicating acceptable efficacy in the initial stages of antibiotic screening. These results confirm that endophytic fungi from the Cyrene region represent a promising source of bioactive compounds with antibacterial activity, particularly against Gram-positive bacteria. Further studies are needed to isolate the active compounds, determine their mechanism of action, and evaluate their efficacy in biological models.